Реакційне спікання кубічного нітриду бору з алюмінієм і тугоплавкими сполуками при високому тиску - Коновал, С.М.; Гарбуз, Т.О.; Беженар, М.П.; Божко, С.А.; Нагорний, П.А.; Білявина, Н.М.; Марків, В.Я. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
Reactionary interacting has been investigated at sintering in carbide and steel apparatuses
of high pressure of cubic nitride of boron composites from a charge cBN–Al and cBN–Al–TiB2 depending on the aluminium content in a charge